Pembangunan Aplikasi Rekod Kesihatan Bayi Secara Berkala - Nur Aimi Nabilah Abdul Halim,; Ramli, Azizul Azhar (Applied Information Technology And Computer Science, 2021)
Aplikasi Rekod Kesihatan Bayi Secara Berkala (myBayi) was developed to facilitate the method of recording baby data online. The management of baby health record is still by record it using books. The use of this method has caused some problems to parents as well as health staff themselves such as loss of baby health record. Based on the shortcomings faced by parents and health staff, the development of the myBayi Application is done to help make it easier for users to check and enter data online which is the latest development of technology today that is more focused on smartphone facilities than manual systems. In addition, this application will provide a platform for doctors to record baby health data every time a health screening appointment occurs, and parents can check their child's information online. This myBayi application will be developed using the Agile methodology. The myBayi application uses Android Studio software, PHPmyAdmin and selects Flutter framework as encoding. Once this application is fully developed, health staff can enter data, generate graphs based on baby reports and parents can check appointments and child records without having to refers on books anymore. Therefore, it is hoped that the myBayi Application can help parents and health staff to use it more easily and systematically.